Extending the Vision of Motivation in Business Ethics and Functional Behaviour - AL-Nuwaybit , Thamer H. (Current Topics on Business, Economics and Finance Vol. 7, 2023)
This chapter motivates followers of the organization to realize with this guide. In other words, we are studying the motivations that motivate us to track this rules. Ethical work is important because it allows employees to touch their goals and their loyalty to work. As a result, moral considerations are overlooked, leading to unethical practises that can harm human rights in the long run. This study will aid in comprehending the major issues concerning the development of ethical culture and functional behaviour in the organisation. This study will help in prominence the importance of business ethics and functional behavior in the organization. When the research will be conducting assessment will be drawn between organizations that have ethics in their culture and those who don’t, and with this motivating factors that can help with business ethics reception in the organization can strongminded. To realize the functional behavior of employees and create effective business ethics policies, it is essential to consider these factors in order to raise revenues in a lawful way.